HUBUNGAN POLA ASUH ORANGTUA DENGAN KECERDASAN INTERPERSONAL ANAK: THE RELATIONSHIP BETWEEN PARENTING STYLES AND CHILDREN'S INTERPERSONAL INTELLIGENCE - Agustina, Resty; Marlina, Leny; Fahmi, Fahmi (Universitas Islam Malang, 2020)
This research is motivated by various types of parenting patterns that parents apply to children so that they can influence the development of children's potential and intelligence, one of which is interpersonal intelligence. The problem in this study is how are parenting patterns, how is the child's interpersonal intelligence and is there a relationship between parenting patterns and children's interpersonal intelligence. The study was conducted at RA Perwanida 4 Palembang. Using correlational methods and product moment correlation analysis techniques. Based on data analysis, it can be seen that the majority of parenting patterns at RA Perwanida 4 Palembang apply authoritarian parenting patterns as many as 21 (52.5%) so that many children's interpersonal intelligence at RA Perwanida 4 is still not developed, namely as many as 17 (42.5%). The correlation results obtained rxy = -0.380 at a significance level of 0.05 with rtable = 0.320. The calculation shows that rhit> rtable, so Ho is rejected, so the hypothesis indicating a relationship between parenting styles and children's interpersonal intelligence is accepted.